2017
DOI: 10.3892/ol.2017.5908
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum protein ERp46 in prostate adenocarcinoma

Abstract: Abstract. Endoplasmic reticulum (ER) protein ERp46 is a member of the protein disulfide isomerase family of oxidoreductases, which facilitates the reduction of disulfides in proteins and their folding. Accumulation of misfolded proteins has been implicated in cancer. The objectives of the present study were to investigate the role of ERp46 in prostate cancer, its expression and its effects on prostate cancer growth. A tissue microarray with human prostate cancer and normal prostate tissue samples was stained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In addition to PDI, Ero1α also oxidizes other PDI family members, such as ERp46 and P5 [49]. ERp46 promotes tumor growth in prostate carcinoma cells [50]; P5 promotes the proliferation of HeLa cells through activating the Wnt/β-catenin signaling pathway [51]. All these PDI homologues contain the a -type catalytic domains; thus, the strategy of disruption of Ero1α-PDI interaction might also be useful to inhibit cancer progression mediated by PDI homologues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PDI, Ero1α also oxidizes other PDI family members, such as ERp46 and P5 [49]. ERp46 promotes tumor growth in prostate carcinoma cells [50]; P5 promotes the proliferation of HeLa cells through activating the Wnt/β-catenin signaling pathway [51]. All these PDI homologues contain the a -type catalytic domains; thus, the strategy of disruption of Ero1α-PDI interaction might also be useful to inhibit cancer progression mediated by PDI homologues.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, varying culture conditions have been used, including different timepoints, inhibitor concentrations and serum levels. Several studies have used the inhibitors on prostate cancer cell lines, and we have used these studies to select our culture conditions for these experiments [ 39 , 40 , 41 , 42 , 43 , 44 ]. Following treatment with tunicamycin for 24 h, we detected levels of the ER stress marker GRP78 and EDEM3 using Western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the overexpression of TXNDC5 resulted in reduced sensitivity to ER stress when exposed to tunicamycin and thapsigargin. However, TXNDC5 knockout human prostate adenocarcinoma 22Rv1 cells lost the ability to upregulate protein disulfide isomerase after tunicamycin-induced ER stress [48]. Notably, during simvastatin-induced cell death through c-Jun N-terminal kinase (JNK) activation in DU145 human prostate cancer cells, TXNDC5 exhibited an opposite effect to vimentin, RAB1B, HMGCR, HNRNPK, NDRG1, and IDI1, as it was downregulated despite an increase in its molecular weight, suggesting significant post-translational modification [50].…”
Section: Txndc5 and Prostate Cancermentioning
confidence: 98%
“…Indeed, TXNDC5 is increased by ADT-induced hypoxia through HIF1A [42]. Duivenvoorden et al found that when TXNDC5 was stably knocked down using shRNA or overexpressed in prostate carcinoma 22Rv1 cells, tumor growth and proliferation in vitro and in BALB/c nude mice were inhibited and accelerated, respectively [47,48]. Additionally, the downregulation and upregulation of TXNDC5 in the corresponding xenografts showed several candidate genes, including NAAA, SH3BP4, and ID1, that were reciprocally up-and downregulated [49].…”
Section: Txndc5 and Prostate Cancermentioning
confidence: 99%